2012
DOI: 10.1002/wsb.115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pregnancy detection methods in live white‐tailed deer

Abstract: Assessing ungulate reproduction is important to biologists for managing populations and predicting trends. We compared efficacy of trans‐abdominal ultrasound and pregnancy‐specific protein B (PSPB) white‐tailed deer (Odocoileus virginianus) pregnancy estimates, respectively, from January to mid‐April 2009–2011 in the south‐central Upper Peninsula of Michigan, USA. We observed a strong agreement (K = 0.68, SE = 0.13, 95% CI = 0.42–0.94) of PSPB and ultrasound in categorizing pregnant and nonpregnant deer. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…, Duquette et al. ). Vaginal implant transmitters contained temperature‐sensitive switches that emitted a unique pulse frequency when expelled during parturition (Carstensen et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, Duquette et al. ). Vaginal implant transmitters contained temperature‐sensitive switches that emitted a unique pulse frequency when expelled during parturition (Carstensen et al.…”
Section: Methodsmentioning
confidence: 99%
“…We manually restrained captured deer and handinjected them with an intramuscular injection of xylazine (100 mg/mL; X-Ject E; Butler Schein Animal Health, Dublin, Ohio, USA) and ketamine (100 mg/mL; Ketaset; Fort Dodge Laboratories, Fort Dodge, Iowa, USA; . We fitted pregnant does with very high-frequency (VHF) radiocollars (Model 2610B, Advanced Telemetry Systems, Isanti, Minnesota, USA; Model 500, Telonics, Mesa, Arizona, USA) and vaginal implant transmitters (VIT; Model 3930, Advanced Telemetry Systems, Isanti, Minnesota, USA; Carstensen et al 2003, Duquette et al 2012. Vaginal implant transmitters contained temperature-sensitive switches that emitted a unique pulse frequency when expelled during parturition (Carstensen et al 2003).…”
Section: Deer Capture and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Because deer captured using Clover traps and rocket nets can experience capture myopathy‐related mortality (Beringer, Hansen, Wilding, Fisher, & Sheriff, ), deer were not included in survival models until 2 weeks postcapture. As yearling deer captured in this study had different patterns in body mass and pregnancy rates than older deer (Duquette, Belant, Beyer, & Jr, & Svoboda, N. J., ), survival analysis was limited to deer >2.5 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest that animal condition can influence deer induction success, because body condition was an influential variable explaining deer induction success. However, because deer in our study area had minimal fat reserves (Duquette et al 2012) and we found no difference in induction time between injection sites, we suggest that muscle mass likely had a greater influence on deer induction rate than did soft tissue (i.e., subcutaneous body fat).…”
Section: Discussionmentioning
confidence: 62%